The Effectiveness of Problem-Based Critical Arabic Reading Integrating Nabawi Peace Values on Students’ Reading Achievement and Self-Efficacy - Setiadi, Samsi; Mahmudah, Ika; Hanifah, Rifda; Mutmainah, Mia; Nafiah, Khotimatun; Masyitoh, Siti (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2026)
Critical reading competence and reading self-efficacy are essential cognitive and affective components in foreign language learning, particularly in Arabic language education, where students must interpret complex linguistic, historical, and ethical texts. However, traditional reading instruction often emphasizes literal comprehension rather than analytical engagement, resulting in limited development of higher-order reading skills and learner confidence. This study investigates the effectiveness of problem-based critical Arabic reading instruction integrating Nabawi peace values in improving students’ critical reading achievement and reading self-efficacy. Employing a quasi-experimental one-group pretest–posttest design, the study involved 21 undergraduate students enrolled in a Critical Arabic Reading course at a public university in Indonesia. The instructional intervention was conducted using authentic Arabic texts related to the Prophet Muhammad’s peace agreements, implemented through Problem-Based Learning stages including problem orientation, critical analysis, collaborative discussion, and reflective evaluation. Data were collected using a critical reading achievement test and a reading self-efficacy questionnaire validated through item-total correlation and reliability analysis (Cronbach’s alpha = .943–.948). Paired-sample t-test results revealed a statistically significant improvement in students’ critical reading achievement (Mpre = 76.86, Mpost = 87.90, t(20) = −4.518, p < .001, Cohen’s d = 0.99) and reading self-efficacy (Mpre = 70.86, Mpost = 81.52, t(20) = −7.522, p < .001, Cohen’s d = 1.64). These findings indicate that problem-based critical Arabic reading integrating Nabawi peace values has a strong positive effect on both cognitive and affective learning outcomes. The integration of problem-based learning and peace-oriented instructional materials promotes analytical reading competence, enhances learner confidence, and fosters meaningful engagement with texts. This study contributes to Arabic language pedagogy by providing empirical evidence supporting a holistic instructional model integrating cognitive skill development, affective empowerment, and value-based learning.